2020
DOI: 10.3389/fonc.2020.01591
|View full text |Cite
|
Sign up to set email alerts
|

An Ultrasound Radiomics Nomogram for Preoperative Prediction of Central Neck Lymph Node Metastasis in Papillary Thyroid Carcinoma

Abstract: This study aimed to establish and validate an ultrasound radiomics nomogram for the preoperative prediction of central lymph node (LN) metastasis in patients with papillary thyroid carcinoma (PTC). Patients and Methods: The prediction model was developed in 609 patients with clinicopathologically confirmed unifocal PTC who received ultrasonography between Jan 2018 and June 2018. Radiomic features were extracted after the ultrasonography of PTC. Lasso regression model was used for data dimensionality reduction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
2
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 68 publications
2
61
2
4
Order By: Relevance
“…In presence studies, radiomics and deep machinery learning are gradually conducted to investigate the CLNM. The highest sensitivity has reach 0.858 in the existing predictive models of CLNM, which is significantly higher than the current situation (lower than 0.5 for predicting CLNM) ( 27 ). It may provide more dependable evidence for performing central lymph node dissection.…”
Section: Discussionmentioning
confidence: 85%
“…In presence studies, radiomics and deep machinery learning are gradually conducted to investigate the CLNM. The highest sensitivity has reach 0.858 in the existing predictive models of CLNM, which is significantly higher than the current situation (lower than 0.5 for predicting CLNM) ( 27 ). It may provide more dependable evidence for performing central lymph node dissection.…”
Section: Discussionmentioning
confidence: 85%
“…Lateral LN metastasis exhibits a higher recurrence rate and a poorer prognosis than central LN metastasis [ 63 , 64 ]. A recent study developed an ultrasound-based radiomics nomogram to assess its predictive value for central neck lymph node metastasis in PTC patients [ 65 ]. The prediction model showed good accuracy, sensitivity, specificity, and AUC values in both the training dataset and validation dataset.…”
Section: Radiomics In Thyroid Cancer Predictionmentioning
confidence: 99%
“…Reviewing similar works on predicting CLNM 13,26,27,35 , our study had a partial difference and takes it a step further. To our knowledge, compared with other works, our data indicated that HT was one of the independent risk factors in promoting CLNM which deserved further evaluation.…”
Section: Discussionmentioning
confidence: 98%
“…Neither multifocality nor BRAF V600E mutation was analyzed to be associated with CLNM which was believed to be the frequent risk factors in lymph node metastasis. These differences were potential due to that approximately 15% of patients did not undergo ne-needle aspiration (FNA) or BRAF V600E testing before the surgery which was a common limitation in recent studies 26,27 . Besides, a relatively smaller sample size compared with other large cohort studies also contributed to this difference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation